The Yin and Yang of Type 1 Regulatory T Cells: From Discovery to Clinical Application - Sayitoglu, Ece Canan; Freeborn, Robert Arthur; Roncarolo, Maria Grazia (Frontiers in Immunology, 2021)
Regulatory T cells are essential players of peripheral tolerance and suppression of inflammatory immune responses. Type 1 regulatory T (Tr1) cells are Foxp3- regulatory T cells induced in the periphery under tolerogenic conditions. Tr1 cells are identified as LAG3+CD49b+ mature CD4+ T cells that promote peripheral tolerance through secretion of IL-10 and TGF-beta in addition to exerting perforin- and granzyme B-mediated cytotoxicity against myeloid cells. After the initial challenges of isolation were overcome by surface marker identification, ex vivo expansion of antigen-specific Tr1 cells in the presence of tolerogenic dendritic cells (DCs) and IL-10 paved the way for their use in clinical trials. With one Tr1-enriched cell therapy product already in Phase I clinical trial in the context of allogeneic hematopoietic stem cell transplantation (allo-HSCT), Tr1 cell therapy demonstrates promising results so far in terms of efficacy and safety. In the current review, we identify developments in phenotypic and molecular characterization of Tr1 cells and discuss the potential of engineered Tr1-like cells for clinical applications of Tr1 cell therapies. More than 3 decades after their initial discovery, Tr1 cell therapy is now being used to prevent graft versus host disease (GvHD) in allo-HSCT and will be an alternative to immunosuppression to promote graft tolerance in solid organ transplantation in the near future.